ANALYSIS OF RAINFALL INTENSITY LEVELS, AIR PRESSURE AND AIR TEMPERATURE IN THE PAOTERE MAKASSAR REGION DURING THE PERIOD OF 2022 - Abidin, Kurniati Kurniati (SAINFIS: Jurnal Sains Fisika, 2024)
Rainfall is the single most prominent climate in the tropics, according to its diversity. However, there are differences in rain characteristics in other places, including Makassar. Based on this, this research was conducted to determine the patterns and intensity levels of rainfall, air pressure, air temperature in the Paotere Makassar area during the 2022 period, as well as to find out the tools used to measure rainfall, air temperature, air pressure. The type of research used is descriptive analysis, which is carried out by collecting data directly, namely measuring weather parameters such as checking air temperature (dry bulb thermometer and wet bulb thermometer), measuring rainfall, observing air pressure at the Paotere Makassar Maritime Meteorological Station. From the results obtained the highest rainfall in 2022 was 748.8 mm which occurred in December, while the lowest rainfall occurred in August and September with a total rainfall of 41.7 mm and 47.9 mm, with total rainfall intensity full year rainfall of 301.167 mm. The monthly average air pressure data is 1010.164 mb and the average daily air temperature that occurs during the 2022 period is 27.6 °C. From these results the pattern and intensity of rainfall that occurs in 2022, namely the monsoonal type rainfall pattern.